Earnings Management and Financial Distress: The Moderating Role of Independent Commissioners in Indonesian Transportation and Logistics Companies - Rina Safitri; Wiwiek Dianawati (Amkop Management Accounting Review (AMAR), 2026)
This study aims to examine the effect of earnings management on financial distress with independent commissioners serving as a moderating variable. The study is motivated by the increasing risk of financial difficulties faced by companies due to post-pandemic economic instability, which may encourage management to engage in earnings management practices. The population consists of transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a purposive sampling method, a final sample of 84 companies with 401 observations was obtained. This study employs a quantitative approach using multiple linear regression analysis and Moderated Regression Analysis (MRA) with IBM SPSS version 32. The results indicate that earnings management has a positive and significant effect on financial distress. These findings suggest that earnings management practices can influence a company's financial condition and increase the likelihood of financial difficulties. Furthermore, the moderation test reveals that independent commissioners are unable to moderate the effect of earnings management on financial distress. This finding indicates that the presence of independent commissioners has not been effective in either strengthening or weakening the relationship between earnings management and financial distress.